Persepsi Komunitas Basket Terkait Pemberlakuan Kebijakan Pemerintah Tentang Pembebasan Penggunaan Masker Pasca Pandemi di Hutan Kota Kaombona Palu - Kalape, Aulia Fattah (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2024)
This research was conducted to determine the perception of the basketball community regarding the implementation of the government's policy on saving the use of masks after the pandemic in Kaombona City Forest, Palu. In this study, the method used is qualitative method. The type of research used is descriptive case study. Interviews with informants to collect data, then analyzing, compiling and simplifying the data. The results in this study are that the perception of the basketball community regarding the government's policy on exempting the use of masks is a policy that is widely approved by people who are visitors to Kaombona Palu City Forest. Because people think that they need to breathe fresh air and also when using mask they are claustrophobic and many people have carried out the government program, namely the vaccination program so that people who often carry out outdoor activities or activities feel grateful for the government policy so that they no longer need to use masks. In this case, existing perceptions are shaped by perciever factors, The Object or The Target, and The Situation. And perception is influenced by functional factors and situational factors.